2019
DOI: 10.1029/2019gl083463
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Seismicity Pattern Due to the 2016 Kumamoto Earthquakes Identify a Highly Stressed Area on the Hinagu Fault Zone

Abstract: A highly stressed area where eventual ruptures have often been observed to nucleate is characterized by low b values of earthquake frequency‐size distribution. Crustal deformation due to the occurrence of large earthquakes causes stress perturbation in nearby regions, so an investigation into spatiotemporal b values can play a crucial role in the distribution of postseismic hazards after the 2016 Kumamoto earthquake sequence along the Futagawa‐Hinagu fault zone, which culminated in the magnitude 7.3 mainshock.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…b-value estimation. Spatial temporal changes in b are known to reflect a state of stress in the Earth's crust 13,15,42 and to be influenced by asperities and frictional properties 24,43 and by an interface locking along subduction zones 26,44,45 . The results of laboratory experiments indicate a systematic decrease in the b-value approaching the time of the entire fracture 11,12,14 .…”
Section: Methodsmentioning
confidence: 99%
“…b-value estimation. Spatial temporal changes in b are known to reflect a state of stress in the Earth's crust 13,15,42 and to be influenced by asperities and frictional properties 24,43 and by an interface locking along subduction zones 26,44,45 . The results of laboratory experiments indicate a systematic decrease in the b-value approaching the time of the entire fracture 11,12,14 .…”
Section: Methodsmentioning
confidence: 99%
“…The mainshock magnitudes were also similar (M7.1 vs. M7.3) and had the strike‐slip mechanisms. It is difficult to pin point the common stress conditions and state of faults that lead to the occurrence of both sequences but some clues may be inferred from the seismicity patterns that preceded and followed both events and can be related to the changes in the stress field (Nanjo, 2020; Nanjo et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that more accumulated stress was released at shallower depths. an afterslip-dominated region and viscoelastic deformation-dominated region (Nanjo et al 2019). They suggested that there was a local increase in the stresses at the boundary between regimes dominated by different postseismic deformation processes based on the aftershock decay law of Utsu (1961) and a seismicity rate model inferred from the stressing history (Dieterich 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The 6 differential stress generally increases as the b-value decreases, and vice versa. Many studies have examined the stress states in various tectonic settings using spatiotemporal b-value distributions (e.g., Chiba 2019Chiba , 2020Ghosh et al 2008;Nanjo and Yoshida 2018;Nanjo et al 2016Nanjo et al , 2019Schorlemmer et al 2004;Schorlemmer and Wiemer 2005;Tormann et al 2015). The highly stressed areas in any tectonic setting, such as regions with a large coseismic slip and large slip deficit rate, are usually characterized by low b-values.…”
Section: B-valuesmentioning
confidence: 99%